Prevalence and characteristics of paediatric burns at the National Reconstructive Plastic Surgery and Burns Centre, Korle Bu Teaching Hospital, Ghana - Alberta Amissah Rockson; Natalie Benjamin-Damons; Sonti Imogene Pilusa (Elsevier, 2024)
Introduction: Burn injuries among children have emerged as a significant global public health concern, accounting for substantial morbidity and mortality worldwide. Low and Middle-Income Countries bear a significant burden of paediatric burn injuries. In Ghana, limited data exists on the prevalence, characteristics and outcomes of paediatric burns. This study provides vital data on the local burden and epidemiology of paediatric burns at Ghana's main burns treatment center. The findings have significant value in informing prevention strategies, allocating resources, and improving quality of paediatric burn care. Study objective: To establish the prevalence and characteristics of paediatric burns injuries in Ghana's leading burn center. Methodology: A retrospective cohort study analyzed data from 662 adult and paediatric patients who presented with burns from all over Ghana between 2020 and 2022. The study encompassed medical records of paediatric burn cases (aged 0-14 years) admitted to the center from January 2020 to December 2022. A purposive sampling technique was used to select cases based on the inclusion criteria and elimination of cases with 20 % missing data. A total of 335 paediatric records were reviewed. Data analytical methods: Descriptive statistics, such as frequencies, mean, percentages were used to establish period prevalence and demographic characteristics of paediatric burns. Chi-square analysis and univariate logistic regression was utilized to explore associations between categorical variables, and predictors of burn outcome. Results: The period prevalence of paediatric burns was found to be 50.6 %. Paediatric burn cases predominantly affected males (57.6 %). Majority of cases fell within the age range of 1 to 5 years (70.1 %). Hot water emerged as the leading cause (58.4 %), whiles superficial partial thickness burns (51.9 %) was the predominant type of burn. Most cases involved burns affecting less than 20 % Total Body Surface Area (59.0 %). Multi-part body injuries were common (87.2 %), with the lower limb being the most affected (25.36 %). The mortality rate was calculated to be 21.0 %. Higher TBSA was a significant predictor of mortality (p < 0.001). Conclusion: This study found a high prevalence of paediatric burns with hot water and foods being the predominant causes. Higher TBSA predicted lower chances of survival. The findings have scientific value in informing prevention strategies, allocating resources, and improving the quality of care.